Script Concordance Test untuk Menilai Kemampuan Penalaran Klinis Dokter: Bagaimana Mengembangkan Butir Soalnya Berdasarkan Standar Kompetensi Dokter Indonesia? - Fundhy Sinar Ikrar Prihatanto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2012)
Background: Some methods have been developed to assess clinical reasoning skill. It must be understood the principals of each method for the selection if will be applied. In the other hand, it is realized that uncertainty is one of medical context that is poorly measured by other traditional test. The script concordance test (SCT) may be a better method of assessing students, who are taught in the context of uncertainty. SCT could differentiate examinees according to levels of experience in various fields of study. SCT have practical relevance for clinical education. The objective of this study is to give guidance in developing SCT based on Indonesian medical doctor competenceMethod: Relevant literatures are selected as basis of recommendations of SCT construction.Results: Developing SCT needs to consider its: principles as basis of development; format of test item to build a suitable test item, scoring system and panel selection accommodate context of uncertainty, and optimization of test item to enhance SCT.Conclusion: SCT provide investigation on clinical reasoning skill of examinee in the difficult by other objective written methods. Several studies have showing SCT capacity in different levels of experience, and in several field of studies with good results. SCT could be as supplement to assess clinical reasoning skill comprehensively, not replacing other clinical competence assessment method absolutely.